Exploring and fostering second graders' mathematical patterning - Asnakew Gared (College of education, Bahir Dar University, 2023)
A teaching experiment was conducted with grade two pupils at the beginning of the 2018/19 academic year to explore and foster their mathematical patterning abilities: creating, and extending patterns, identifying units of repeat and its length, and predict terms of given patterns. The teaching experiment was conducted at a particular government primary school found in Bahir Dar City Administration. Twenty-five pupils (from seven to thirteen years old) who got parental permission to come school in the opposite school shifts were taken as participants of the study. These pupils sat in groups of five and each group was provided with matchsticks, beads with different sizes, bottle tops, and counters with different shapes and colors. The teaching experiment was conducted in two periods each lasting two and half an hour. Data have been gathered using task-based group interviews, field notes, observations, and pupils' sample works captured through mobile camera. Provided with parallel models (an analogy) for repeating patterns, they created many and even complex repeating patterns. They can easily extend given patterns, and determine the unit of repeat and its length but predicting terms was difficult for them except for patterns with length of core unit two.